Kinetic study of peanut seed oil extraction with supercritical CO2 (Research, Society and Development, 2022)
Due to the need to create new technologies for the production of biofuels, there are techniques to perform oil extraction from oilseeds, such as the supercritical extraction method using CO2, where the seed used to carry out the study (peanut) is subjected to CO2 at high pressures and temperatures, thus becoming a supercritical fluid and carrying out the process of extracting the oil from the seed to produce biodiesel more efficiently. There is another extraction technique in which organic solvents are used. Still, this method has some difficulties that end up causing damage to the environment as it is a process that consumes a significant amount of time and energy. Peanut is the world's fourth-most cultivated oilseed, with large plantations in the Americas, Africa, and Asia. Its planting is carried out to produce grains, oil, and bran. CO2 has interesting physicochemical properties since it is an inert, non-polar, non-flammable, odorless, tasteless gas and has critical parameters and low value. It has a critical pressure of 72.01 bar and a critical temperature of 31.1 °C. The present work presents data from a kinetic study of the supercritical extraction of peanut oil under pressure and temperature conditions of 200 bar, 280 bar, 40 °C, and 60 °C. This project uses an experimental matrix to help carry out the experiments. At the end of the experiments, we obtained a yield of 30% in the supercritical method (80 min) and a percentage yield of 26% by Soxhlet using ethanol as a solvent for 480 minutes.